INANCIAL FEASIBILITY OF CRAB NET CATCHING UNIT IN GALESONG SUBDISTRICT TAKALAR DISTRICT - Yusuf, Djumran; Amiluddin, Amiluddin; RezkiHikmawati, Sri (Torani Journal of Fisheries and Marine Science, 2015)
Appliance catch which is suited for catching existing crab type in coastal territorial water is called the gill net withone sheet or gill net. This research aim to know: (1) kind andinvesment needed at arrest unit crab net, and (2)financial feasibility arrest unit crab net.This research was executed in January until February 2015inGalesongSubdistrictTakalarDistrict with MappakalompoVillage aslocation sample. This research use the surveymethod with the amount sample as much 40 fishermen crab netwho are taken with simple random samplingmethod.Analysis used by descriptive analysis of investment and financial feasibility analysis that areNetPresentValue (NPV), Net Benefit Cost Ratio(Net B/C) andInternal Rate of Return (IRR). Result of Research indicatethat total of investment cost atarrest unit crab net that is equal to IDR 13.414.500with larger investment cost isboatpurchasing andarrest unit crab net is feasible to be developedbecause result of financial analysisNPV >0(IDR177,103,595.7), Net B/C > 1 (13.2)and IRR >interest rate (64%).Key words: catching, fishermen, crab nets, investment, financial feasibility